ДВУЕДИНАЯ ВРАЧЕБНАЯ ТАКТИКА ПРЕДУПРЕЖДЕНИЯ НИЗКОЭНЕРГЕТИЧЕСКИХ ПЕРЕЛОМОВ У ЛИЦ ПОЖИЛОГО ВОЗРАСТА — ЛЕЧЕНИЕ ОСТЕОПОРОЗА И ПРОФИЛАКТИКА ПАДЕНИЙ - С. П. Филоненко; С. С. Якушин (Архивъ внутренней медицины, 2014)
Until recently low-energy fractures in the elderly associated primarily with osteoporosis, not paying enough attention to the prevention of falls. The rationale for the use of combination therapy consisting of treatment of osteoporosis (bisphosphonates) and prevention of falls (alfacalcidol, calcitriol, non-drug methods) in order to prevent fractures in the elderly.